(untitled) (Al-Academy, 2017)
Arabic calligraphy has great importance in the printing designs that are often on the written character-based to perform functional goals and to achieve some of the aesthetic values ​​in design work, has led major developments in the field of computer manufacturing and design software for the design and layout to increase to deal with the programmed character for the purposes of typesetting has confronted this Find the Arab character programmed for the purposes of typesetting for the detection of the most important design interventions that underwent the Arabic letter written to turn it into a programmed image intended for the purposes of the printing and typesetting has been addressed in the context of which the theoretical types of Arabic calligraphy as a prelude to enter the back line of presenting the history and aesthetics and graphic character and methods of typesetting typesetting computer and then Turning the theoretical framework to the most important word processing and how to divide the design copies a character where programs, researcher has an inventory of the research community, which is (108) character drew them (19) characters sample deliberate analyzed has concluded a number of findings and conclusions including: lack of knowledge workers in the design of the character rules of Arabic calligraphy. The absence of the aesthetic and the flexibility and suppleness and cruise, which is characterized by the Arabic letter obscenities manually features. Failure to observe the design of processors used by the designer to address the letters in the designs, which caused a clear influence on the functional character. The researcher offers a number of suggestions and recommendations to address the negatives reached by the results of his research